1985
DOI: 10.1037/0022-006x.53.5.679
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of posttreatment alcoholics' drinking patterns.

Abstract: Many clinical practices are based on the assumption that the posttreatment drinking of alcoholics is consistent and predictable over fairly substantial periods of time. Using a sample of 98 alcoholics, we studied the intercorrelations between controlover-drinking ratings made in 10 follow-ups covering the first 18 months after treatment. The intercorrelations were surprisingly low, particularly for periods beginning during the 1st month after discharge. Thus, it appears that control among treated alcoholics is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Second, there is ample empirical evidence that problem drinkers change from one drinking status to another during posttreatment followup (e-g., Watson & Pucel, 1985;Yates & Norris, 1981). Performing several assessments of drinking during a longitudinal study would provide the researcher with an estimate of the stability of a subject's drinking status.…”
Section: Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, there is ample empirical evidence that problem drinkers change from one drinking status to another during posttreatment followup (e-g., Watson & Pucel, 1985;Yates & Norris, 1981). Performing several assessments of drinking during a longitudinal study would provide the researcher with an estimate of the stability of a subject's drinking status.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…In other studies, however, CD was sustained during follow-up periods of at least 1 year (e.g., Miller & Baca, 1983;Pettinati, Sugarman, DiDonato, & Maurer, 1982;Polich et al, 1981;Vaillant & Milofsky, 1982). Instability of drinking is not confined to CD in any case, and many alcoholics' drinking patterns-whether controlled, abstinent, or uncontrolled-change several times within a matter of months or years (e.g., Watson & Pucel, 1985;Yates & Norris, 1981).…”
mentioning
confidence: 92%
“…Although the quantity and frequency of drinking often change during follow-up (J. R. Taylor, 1987; Watson & Pucel, 1985; Yates & Norris, 1981), success per se (i.e., either controlling one's drinking or abstaining) has been predictive of continued success. Maisto et al (1980) found that “days functioning well” (controlled plus abstinent days) during the final 6 months of a 2-year follow-up was predicted by the same index in the previous 6 months.…”
Section: Other Predictorsmentioning
confidence: 99%
“…In other studies, however, CD was sustained during follow-up periods of at least 1 year (e.g., Miller & Baca, 1983; Pettinati, Sugarman, DiDonato, & Maurer, 1982; Polich et al, 1981; Vaillant & Milofsky, 1982). Instability of drinking is not confined to CD in any case, and many alcoholics' drinking patterns—whether controlled, abstinent, or uncontrolled—change several times within a matter of months or years (e.g., Watson & Pucel, 1985; Yates & Norris, 1981). Uncontrolled drinking is a frequent occurrence following periods of both abstinence and CD, and periods of relapse are likely whether an alcoholic attempts CD or abstinence.…”
mentioning
confidence: 99%
“…Indeed, the length of follow-up in treatment outcome studies varies from several weeks to several years (see reviews by Ivanoff & Stem, 1992;Nicholson & Berman, 1983;Smith, Glass, & Miller, 1980). For problems which have a chronic and cyclical course with periods of relapse and recovery, such as substance abuse, longer follow-up periods are necessary (Brown, Vik, & Creamer, 1989;Farrington, 1992;Green & Hergert, 1989;Kazdin, 1987;Milkman, Weiner, & Sunderwith, 1984;Vaillant & Milofsky, 1982;Watson & Purcell, 1985). Consequently, some have argued that drug and alcohol abuse treatment outcome studies should include follow-up assessments at least 1 year after termination (Davidge & Forman, 1988;Lambert, Shapiro, & Bergin, 1986;O'Farrell, 1992).…”
Section: Next Previous Firstmentioning
confidence: 99%